Fodor's essential France 2024 - Gauldie, Robin; Heslin, Nancy; Inman, Nick; Ladonne, Jennifer; Monaco, Emily; Parry, Lyn; Power, Virginia (Travel writer); Skelton, Tim; Vadino, Diane; Vermee, Jack (Fodor's Travel, a division of MH Sub I, LLC, dba Internet Brands, 2023)
"Ready to go away? The experts at Fodor's are here to help. We're bringing you the very best of France, including Paris, Provence, Normandy, the Riviera, Brittany, and more. Our local experts vet every recommendation to ensure that you have all the essential information to plan a perfect trip and make the most of your time"--Page 4 of cover.